PEMBUATAN TEH DARI DAUN GAHARU JENIS Gyrinops versteegii - Taufik Samsuri; Herdiyana Fitriani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
Gaharu is a product of Non Timber Forest which is very potential and high economic value in West Nusa Tenggara Province. Lombok Island is one of the gaharu producing areas in Indonesia and is a growing place of endemic gaharu commercial species such as Gyrinops versteegii. Local people call it